10.1016/s1544-8800(05)70353-5 (CrossRef Listing of Deleted DOIs, 2000)
To evaluate, in a post hoc subanalysis, the effects of cannabidiol (CBD)-rich cannabis oil on facial expression recognition and theory of mind in children with autism spectrum disorder (ASD). This post hoc subanalysis included children from a double-blind, randomized, placebo-controlled trial who completed social cognition assessments at baseline and after treatment. Participants received CBD-rich cannabis oil or placebo for 12 weeks. Facial expression recognition and theory of mind were assessed using neuropsychological tasks. Between-group differences were evaluated using the Mann-Whitney U test, whereas within-group changes were assessed using the Wilcoxon signed-rank test. Nineteen Brazilian children with ASD were included (72.7% male; mean age, 7.82 years). Within-group analyses showed significant improvements in facial expression recognition (p = 0.030) and verbal theory of mind (p = 0.016) after treatment in the CBD group, whereas corresponding changes in the placebo group were not statistically significant. However, between-group comparisons showed no significant differences after treatment in facial expression recognition (p = 0.527) or verbal theory of mind (p = 0.901). Total theory of mind scores improved significantly within both groups, with no significant between-group difference (p = 0.967). Although significant within-group improvements in facial expression recognition and verbal theory of mind were observed following CBD-rich cannabis oil treatment, these changes were not significantly different from those observed with placebo. Given the small sample size and exploratory post hoc design, these findings should be interpreted cautiously and do not establish a treatment effect of CBD on social cognition in children with ASD. TRIAL REGISTRATION: Brazilian Clinical Trials Registry (ReBEC), RBR-5wr2cqq (UTN: U1111-1261-4178), accessible at https://ensaiosclinicos.gov.br/rg/RBR-5wr2cqq.